Effect of denture liners surface modification with Equisetum giganteum and Punica granatum on Candida albicans biofilm inhibition - Garcia, Cindy Ruiz; Ueda, Thaís Yumi; da Silva, Rafaela Alves; Cano, Isadora Prado; Saldanha, Luiz Leonardo [UNESP]; Dokkedal, Anne Lígia [UNESP]; Porto, Vinicius Carvalho; Urban, Vanessa Migliorini; Neppelenbroek, Karin Hermana (Taylor & Francis, 2022)
Aim: This study investigated the effect of denture liners surface modification with Equisetum giganteum (EG) and Punica granatum (PG) on Candida albicans biofilm inhibition supposing its usage as a sustained-release therapeutical delivery system for Candida-associated denture stomatitis. Materials & methods:C. albicans biofilm (SC5314 or ATCC 90028) was formed on soft liners superficially modified by a primer mixed to drugs at minimum inhibitory concentrations (0.100 g for EG and PG or 0.016 g for nystatin per ml of primer). After 24 h, 7 or 14 days, antibiofilm activity was evaluated by colony-forming unit counts. Results: Not all groups were equi-efficient to nystatin after 24 h and 7 days. After 14 days, EG and PG efficacies were not different from nystatin (almost 100% inhibition). Conclusion: The proposed protocol presents a promising option to allopathic drugs for Candida-associated denture stomatitis treatment.
Keywords: antimicrobial agents; Candida albicans; denture liners; denture stomatitis; natural products